Local Community Participation in Management of Batur Natural Hot Spring as a Tirta Tourist Attraction in Kintamani, Bangli Regency - Wiramatika, I Gede; Sumardani, Rizki (Jurnal Manajemen Pelayanan Hotel, 2024)
The Batur Natural Hot Spring tourist attraction is one of the hot spring tourist attractions in Kintamani and isbelieved to cure skin diseases. The development of Batur Natural Hot Spring as a tourist attraction cannot beseparated from the participation of the local community. Local community participation can be said to be oneof the important aspects of tourism activities to support improving the standard of living of the local Baturcommunity in particular. This research aims to determine the form of local community participation inmanaging the Batur Natural Hot Spring tourist attraction. This research is qualitative research that focuses onlocal community participation. The data in this research was collected through observation, interviews,literature study, and documentation methods. The informal determination technique uses the AccidentalSampling technique, and the data analysis technique uses qualitative descriptive data analysis techniques. Theresults of this research show that local community participation in developing the Batur Natural Hot Springtourist attraction appears to play a very active role which can be seen starting from the planning stage,implementation stage, and evaluation stage.Keywords: Tourism, Participation, Local community